Faktor-faktor yang Mempengaruhi Kemampuan Usaha Kecil Menengah (UKM) Menembus Pasar Luar Negeri’(Studi pada UKM Kerajinan di Gamplong Moyudan Sleman Yogyakarta) - Sigit Haryono (Jurnal Paradigma, 2011)
This study aims to determine the factors that hinder SMEs to penetrate overseas markets. The study was conducted in Gamplong, Moyudan, Sleman, Yogyakarta. This research is disciptive qualitative.The results showed that factors that inhibit the ability of SMEs penetrate the overseas market is the model. The cost of big promotion, a limited knowledge of export, limited skills and lack of the capacity to produce in large scale